2016
DOI: 10.2355/isijinternational.isijint-2015-485
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Phase Formation and Zinc Removal during Sintering of Filter Cake Wastes

Abstract: A large amount of filter cake wastes are produced from the gas cleaning systems of blast furnace (BF) ironmaking and basic oxygen furnace (BOF) steelmaking processes. The filter cake wastes cannot be directly recycled through the ironmaking process due to the high zinc contents and are therefore, predominantly, stockpiled. The storage of filter cake wastes presents a long-term environmental issue but also an opportunity to extract or recover the iron content, motivating a search for processes or technologies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In terms of laboratory-based sintering investigations, there are two generally accepted experimental scales utilized prior to industrial-scale trials being undertaken, viz. bench-scale tablet (compact) testing [3][4][5][6][7], and pilot-scale pot testing [2,[8][9][10][11][12]. The former has the advantages of flexibility and more precise control of sintering conditions, but the effects of particle size and heterogeneity of the blend are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of laboratory-based sintering investigations, there are two generally accepted experimental scales utilized prior to industrial-scale trials being undertaken, viz. bench-scale tablet (compact) testing [3][4][5][6][7], and pilot-scale pot testing [2,[8][9][10][11][12]. The former has the advantages of flexibility and more precise control of sintering conditions, but the effects of particle size and heterogeneity of the blend are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the increasing consumption of high-alumina iron ores, the investigations focused on the role of Al 2 O 3 in the formation and crystallization of the binding phase have increased substantially [ 6 , 7 , 8 ]. Researchers [ 9 , 10 , 11 ] have found that adding a moderate quantity of Al 2 O 3 can promote the formation of complex calcium ferrite.…”
Section: Introductionmentioning
confidence: 99%